2022
DOI: 10.1186/s12884-022-04411-w
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding among women with type 1 and type 2 diabetes mellitus

Abstract: Objective To compare exclusive breastfeeding (BF) and BF initiation among 185 women with Type 1 and 212 women with Type 2 pregestational diabetes who intended exclusive or partial BF and delivered at ≥34 weeks of gestation. Methods Retrospective cohort study. At discharge, exclusive BF is direct BF or BF complemented with expressed breast milk. BF initiation is defined by exclusive or partial BF. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…In a recent study of maternity care practices and policies in 1,305 hospitals in the United States, the mean in-hospital EBF rate for infants in the general population was 51.4% [ 6 ]. Recently, we reported EBF rates in women with mild CHTN (47%) and with severe CHTN (50%) [ 25 ], with preeclampsia (39%) and with severe preeclampsia (37%) [ 26 ], with preeclampsia superimposed on pregestational diabetes (18%) [ 27 ], with CHTN superimposed on pregestational diabetes (19%) [ 28 ], and with pregestational diabetes with prior BF experience (33%) and without prior BF experience (11%) [ 9 ]. In line with the above, the low EBF rates associated with e xcessive GWG for Type 1 and Type 2 (27%), prior BF experience (33%), Grade 1 obesity (28%), Grade 2 (33%) and Grade 3 (22%) reported here are similar to those of women with pregestational diabetes and superimposed comorbidities described above [ 9 , 25 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study of maternity care practices and policies in 1,305 hospitals in the United States, the mean in-hospital EBF rate for infants in the general population was 51.4% [ 6 ]. Recently, we reported EBF rates in women with mild CHTN (47%) and with severe CHTN (50%) [ 25 ], with preeclampsia (39%) and with severe preeclampsia (37%) [ 26 ], with preeclampsia superimposed on pregestational diabetes (18%) [ 27 ], with CHTN superimposed on pregestational diabetes (19%) [ 28 ], and with pregestational diabetes with prior BF experience (33%) and without prior BF experience (11%) [ 9 ]. In line with the above, the low EBF rates associated with e xcessive GWG for Type 1 and Type 2 (27%), prior BF experience (33%), Grade 1 obesity (28%), Grade 2 (33%) and Grade 3 (22%) reported here are similar to those of women with pregestational diabetes and superimposed comorbidities described above [ 9 , 25 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data also showed that women with excessive GWG and no prior BF experience had the lowest EBF at discharge. A positive BF experience improves attitude, confidence, self-efficacy, motivation and intention to BF [ 9 , 34 ]. Negative BF experiences are related to maternal or neonatal morbidities, to difficulties inherent to lactation such as perception of low milk supply, suck or latch problems, mastitis or nipple fissures [ 9 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations